Sustainable bioprocessing of various biomass feedstocks: 2,3-butanediol production using novel pretreatment and fermentation - Guragain, Yadhu Nath (Kansas State University, 2015)
Lignocellulosic biomass feedstocks are a sustainable resource required for rapid growth of bio-based industries. An integrated approach, including plant breeding, harvesting, handling, and conversion to fuels, chemicals and power, is required for the commercial viability of the lignocellulosic-based biorefineries. Optimization of conversion processes, including biomass pretreatment and hydrolysis, is a challenging task because of the distinct variations in composition and structure of biopolymers among biomass types. Efficient fermentation of biomass hydrolyzates comprising of different types of sugars is challenging. The purpose of this doctoral research was to evaluate and optimize the various processing steps in the entire the biomass value chain for efficient production of advanced biofuels and chemicals from diverse biomass feedstocks. Our results showed that densification of bulky biomass by pelleting to better streamline the handling and logistic issues improved pretreatment and hydrolysis efficiencies. Alkali pretreatment was significantly more effective than acid pretreatment at same processing conditions for grass and hardwood. The ethanol-isopropanol mixture, and glycerol with 0.4% (w/v) sodium hydroxide were the promising organic solvent systems for the pretreatment of corn stover (grass), and poplar (hardwood), respectively. None of the pretreatment methods used in this study worked well for Douglas fir (softwood), which indicates a need to further optimize appropriate processing conditions, better solvent and catalyst for effective pretreatment of this biomass. The brown midrib (bmr) mutations improved the biomass quality as a feedstock for biochemicals production in some sorghum cultivars and bmr types, while adverse effects were observed in others. These results indicated that each potential sorghum cultivar should be separately evaluated for each type of bmr mutation to develop the best sorghum line as an energy crop. Development of an appropriate biomass processing technology to generate separate cellulose and hemicellulose hydrolyzates is required for efficient 2,3-butanediol (BD) fermentation using a non-pathogenic bacterial strain, Bacillus licheniformis DSM 8785. This culture is significantly more efficient for BD fermentation in single sugar media than Klebsiella oxytoca ATCC 8724. Though K. oxytoca is a better culture reported so far for BD fermentation from diverse sugars media, but it is a biosafety level 2 organism, which limits its commercial potential.
Keywords: Lignocellulosic biomass; Pretreatment; Hydrolysis; Fermentation; 2,3-Butanediol; Alternative Energy (0363); Chemistry, Agricultural (0749); Food Science (0359)